Incidence of adverse drug reactions in a paediatric ward of a Malaysian hospital: A prospective observational study - Ithnin, M; Rani, MDM; Abd Latif, Z; Kani, PAP; Syaiful, A; Mohd, TAMT; Khairun Nain Nor Aripin (Pharmacotherapy Group, 2024)
Purpose: To investigate the incidence, characteristics and risk factors of adverse drug reactions (ADRs) in hospitalized children in a Malaysian hospital. Methods: Patients admitted to the Paediatric Department of Hospital Ampang in Kuala Lumpur, Malaysia were monitored for occurrence of ADRs by spontaneous reporting or daily review of their case notes. Characteristics of ADRs were categorised and ADRs were analysed for causality, severity and preventability. Multivariate analyses were performed to determine associations between certain selected risk factors and ADR occurrence. Results: In 423 paediatric patients admitted in Hospital Ampang (436 admissions), the ADR incidence rate was 80 % (95 % CI, 5 - 11 %). The most commonly involved medications were systemic antibacterial drugs (77.4 %). About 61.3 % of the ADRs were of probable causality and 12.9 % were definitely preventable No severe ADRs were detected, with 41.9 % being moderate and 58.1 % being mild, based on a severity scale Younger children (OR = 3.387, 95 % CI, 1.377, 8.334) and the number of systemic antibacterial drugs given (OR = 1.469, 95 % CI 1.201, 1.798) were potential risk factors associated with ADRs. Conclusion: ADRs occur at a significant rate in the Malaysian children admitted to the hospital studied. Further studies are needed to provide drug safety data for the paediatric population in Malaysia.